Seeing the forest for the trees: A social-ecological systems approach to managing outdoor recreation visitation in parks and protected areas. (June 2022) - Ferguson, Michael D.; Giles, Georgia; Ferguson, Lauren A.; Barcelona, Robert; Evensen, Darrick; Barrows, Courtney; Leberman, Marianne
Abstract: Parks and protected areas visitation in the United States has increased substantially over the past several decades, and dramatically within the past few years. This expansion in visitation raises concerns regarding the influence of social, situational, and ecological factors upon visitor behaviors, decision-making, and overall experiences. This study investigated the relationship between three influencing factors and visitors' coping behaviors and overall satisfaction on the White Mountain National Forest (WMNF) of New Hampshire. A mail-back and online survey method was used to collect data from WMNF visitors from June to September of 2020 ( n  = 642). Structural equation modeling and binary logistic regression analyses suggest social factors (e.g., crowding and conflict), situational factors (e.g., litter and access), and ecological factors (e.g., weather and seasonality) were significant predictors of visitor decision-making and overall satisfaction on the WMNF. Moreover, a majority of the sample consistently employed behavioral adaptations such as resource and temporal substitution, and in some instances, permanently abandoned their recreation experiences altogether, all in an effort to maintain satisfaction. This study demonstrates that in addition to social factors, situational and ecological factors should also be integrated when assessing the broader human-nature relationship. This research advances the social-ecological systems framework and suggests the importance of considering the interconnectivity between recreation visitor experiences and natural resources when sustainably managing parks and protected areas. Management implications: This study found that social, situational, and ecological factors are driving the need for visitor substitution behaviors on the WMNF. Resource and temporal substitution were most common, with an approximate 95% probability of visitor engagement. Results indicate visitors are able to effectively cope with situational and ecological impacts, partially cope with crowding impacts, and unable to cope with conflict related impacts. These findings suggest visitor conflict, followed by crowding, should be prioritized by resource managers. Additionally, resource managers should work with adjacent communities and stakeholders on communication and engagement strategies, especially in areas proximate to recreation sites prone to crowding and conflict.